The role of cybersecurity in state stability - Mahdi, Saima Ali (The International and Political Journal, 2025)
Cybersecurity is not just a technical issue but a fundamental pillar of political and social stability. In Iraq, enhancing cyber capabilities is a vital step to protect democracy, combat terrorism, attract investments, and build citizens’ trust in state institutions. Today, the internet is capable of sending and receiving any form of data, and without an effective cybersecurity strategy, the country remains vulnerable to threats that could lead to insecurity and long-term instability.